2020
DOI: 10.1103/physrevd.101.043529
|View full text |Cite
|
Sign up to set email alerts
|

Primordial non-Gaussianities of scalar and tensor perturbations in general bounce cosmology: Evading the no-go theorem

Abstract: It has been pointed out that matter bounce cosmology driven by a k-essence field cannot satisfy simultaneously the observational bounds on the tensor-to-scalar ratio and non-Gaussianity of the curvature perturbation. In this paper, we show that this is not the case in more general scalartensor theories. To do so, we evaluate the power spectra and the bispectra of scalar and tensor perturbations on a general contracting background in the Horndeski theory. We then discuss how one can discriminate contracting mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…The "no-go" theorem proved in [56,57] indicates that pathological instabilities of perturbations appear in either the NEC-violating period or sooner or later in spatial flat nonsingular cosmology constructed by Horndeski theory [58][59][60], see also [61][62][63][64][65][66][67][68][69]. It is then demonstrated explicitly with the EFT method [70][71][72][73][74] that fully stable NEC-violating nonsingular cosmological models can be constructed in "beyond Horndeski" theories [75,76], see [77][78][79][80][81][82][83][84][85][86][87][88][89][90] for later developments. Notably, the physics represented by higher derivative "beyond Horndeski" operators plays an essential role in realizing fully stable NEC-violating nonsingular cosmology.…”
Section: Jhep10(2022)140mentioning
confidence: 97%
“…The "no-go" theorem proved in [56,57] indicates that pathological instabilities of perturbations appear in either the NEC-violating period or sooner or later in spatial flat nonsingular cosmology constructed by Horndeski theory [58][59][60], see also [61][62][63][64][65][66][67][68][69]. It is then demonstrated explicitly with the EFT method [70][71][72][73][74] that fully stable NEC-violating nonsingular cosmological models can be constructed in "beyond Horndeski" theories [75,76], see [77][78][79][80][81][82][83][84][85][86][87][88][89][90] for later developments. Notably, the physics represented by higher derivative "beyond Horndeski" operators plays an essential role in realizing fully stable NEC-violating nonsingular cosmology.…”
Section: Jhep10(2022)140mentioning
confidence: 97%
“…[74,75], authors discussed that in matter bounce scenario driven by Horndeski theory, one could not get small r while keeping f nl small enough to be within the current constraints (a.k.a. no-go theorem), while it is also interesting to consider such constraints for other early universe scenarios/models (examples has been given in [76]). We will address the above discussion in future works.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in [90], it is found that the new physics at the bouncing phase has negligible contribution to the power spectrum. Consequently, in many studies of non-singular cosmology [96][97][98][99][100][101][102][103], the signals from the bouncing phase are small, the main phenomenological contribution comes from the contraction phase, so it's difficult to probe the new physics in bouncing phase 1 . Specifically, in previous literature addressing the parity-violation effect in bouncing cosmology [10], the bouncing phase is directly replaced by a simple junction condition so there is only a contraction and an expansion in their scenario.…”
Section: Introductionmentioning
confidence: 99%